Mechanism of Stochastic Resonance in a Quorum Sensing Network Regulated by Small RNAs - Ya-nan Zhu; Jianwei Shen; Yong Xu (Abstract and Applied Analysis)
Bacterial quorum sensing (QS) is an important process of cell communication and more and more attention is paid to it. Moreover, the noises are ubiquitous in nature and often play positive role. In this paper, we investigate how the noise enhances the QS though the stochastic resonance (SR) and explain the mechanism of SR in this quorum sensing network. In addition, we also discuss the interaction between the small RNA and the other genes in this network and discover the biological importance.